Succinate/NLRP3 Inflammasome Induces Synovial Fibroblast Activation: Therapeutical Effects of Clematichinenoside AR on Arthritis - Li, Yi; Zheng, Jia-Yi; Liu, Jian-Qun; Yang, Jie; Liu, Yang; Wang, Chen; Ma, Xiao-Nan; Liu, Bao-Lin; Xin, Gui-Zhong; Liu, Li-Fang (Frontiers in Immunology, 2016)
Clematichinenoside AR (C-AR) is a triterpene saponin isolated from the root of Clematis manshurica Rupr., which is a herbal medicine used in traditional Chinese medicine for the treatment of arthritis. C-AR exerts anti-inflammatory and immunosuppressive properties, but little is known about its action in the suppression of fibroblast activation. Low oxygen tension and TGF-β1 induction in the synovium contribute to fibrosis in arthrits. This study was designed to investigate the effect of clematichinenoside AR (C-AR) on synovial fibrosis from the aspects of hypoxic TGF-β1 and HIF-1α induction. In the synovium of rheumatoid arthritis rats, hypoxic TGF-β1 induction increased succinate accumulation due to the reversal of SDH activation and induced NLRP3 inflammasome activation in a manner dependent on HIF-1α induction. In response to NLRP3 inflammsome activation, the released IL-1β further increased TGF-β1 induction, suggesting the forward cycle between inflammation and fibrosis in myofibroblast activation. In the synovium of rheumatoid arthritis rats, C-AR inhibited hypoxic TGF-β1 induction and suppressed succinate-associated NLRP3 inflammasome activation by inhibiting SDH activity, and thereby prevented myofibroblast activation by blocking the cross-talk between inflammation and fibrosis. Taken together, these results showed that succinate worked as a metabolic signaling, linking inflammation with fibrosis through NLRP3 inflammasome activation. These findings suggested that synovial succinate accumulation and HIF-1α induction might be therapeutical targets for the prevention of fibrosis in arthritis.